Clustering Techniques Used in Vehicular Ad-hoc Network: A Survey - Rani, Megha; Saxena, Akash (International Journal of Computer Sciences and Engineering, 2025)
VANET has become one of the active areas of research and development these days. As communication among the vehicles is one of the challenging tasks in a highly dynamic environment. Many of the clustering algorithms have been implemented for providing the secured communication between vehicles within a cluster. Generally Clustering consists of different nodes like mobile devices, vehicles, sensors, etc. that are grouped together according to some predefined rules. A group of nodes within a cluster can communicate with each other securely and without disconnection. The important task of the clustering algorithm is to achieve the cluster stability. Here different categories of clustering algorithm are highlighted, such as the significance of various approaches with their objectives.